Effect of Heating Fuel through the Upper Tank Radiator with Copper Pipes Against Torque and Power - Endrika Wahidri; Erzeddin Alwi; Remon Lapisa (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2019)
In an effort to improve motorcycle performance is done in various ways, one of which fuel warming through upper radiator tank with copper pipe. Before the fuel is mixed with air. Fuel can evaporate and betekanan, so as to accelerate and multiply income mixing fuel and air in the carburetor in hopes of improving engine performance. The test results of heating fuel towards the torque and power of motorcycles 110 cc Honda Vario using dyno test. Indicates that, the fuel warming influence on the torque and power of motorcycles in four steps. The average torque at 6500 rpm engine rounds without a heater of 6.72 Nm with an average torque at 6500 rpm engine using fuel warming through upper radiator tank with copper pipe of 7.07 Nm. With the increased torque of 0.35 Nm or 4.95%. While the average Power without the heater on the engine rpm of 8000 rounds 6.3 HP with average power use of heating fuel through the upper radiator tank with copper pipe of 6.8 HP at 8000 rpm engine rotation. With the increased power of 0.5 or 7.35%.